2022
DOI: 10.3390/jcm11071850
|View full text |Cite
|
Sign up to set email alerts
|

Hospital at Home for Elderly COVID-19 Patients: A Preliminary Report with 100 Patients

Abstract: Hospital-at-home (HaH) care is useful for patients with COVID-19 and an alternative strategy when hospital capacity is under pressure due to patient surges. However, the efficacy and safety of HaH in elderly patients with COVID-19 remain unknown. In Kyoto city, we conducted a retrospective medical record review of HaH care focused on elderly COVID-19 patients from 4 February to 25 June 2021. Eligible patients were (1) COVID-19 patients aged ≥70 years and those who lived with them or (2) COVID-19 patients aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…Consistent with previous studies, our results showed that our HaH care model for COVID-19 patients is a useful alternative to alleviate the shortage of hospital staff and beds (7, 9-12). We further suggested that such models could be built by multiple clinics that normally provide primary care services.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies, our results showed that our HaH care model for COVID-19 patients is a useful alternative to alleviate the shortage of hospital staff and beds (7, 9-12). We further suggested that such models could be built by multiple clinics that normally provide primary care services.…”
Section: Discussionsupporting
confidence: 92%
“…To reduce the burden on hospitals, it is crucial to triage the patients who require immediate hospitalization and to provide care for COVID-19 patients in the primary care setting rather than in hospital. We previously reported the usefulness of HaH care without hospital visits for elderly COVID-19 patients in Kyoto city (12). This provision of HaH care in a primary care clinic that combines the functions of triage and inpatient care is unique worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high case-fatality rate of patients during the Alpha wave may be because the service catered to old patients during this period. Previous studies have reported the establishment of HaHs during the COVID-19 pandemic [ 8 , 22 , 23 , 24 ]; one HaH service treated moderate COVID-19 patients [ 8 , 24 ], whereas others treated old and severe patients [ 23 ]. The young age and low case-fatality rate among patients treated by the AHHC service during the Delta wave was reflective of the national trend [ 25 ] and is thought to be primarily attributable to the success of vaccination, rather than an improvement in the AHHC service.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the oxygen monitoring programmes also existed as part of a wider package of remote monitoring, for example, including thermometers and blood pressure devices or including additional symptom monitoring [29 & ]. Supplemental oxygen therapy has been described as part of relatively few remote monitoring pathways, used either to prevent the need for admission to hospital or to facilitate early supported discharge from hospital [16,[30][31][32]. Some pathways were designed solely for those requiring home oxygen therapy, whereas others offered home oxygen therapy as part of a wider oximetry monitoring programme.…”
Section: Purpose and Scope Of Home Oxygen Monitoring And Therapy Prog...mentioning
confidence: 99%
“…Supplemental oxygen therapy has been described as part of relatively few remote monitoring pathways, used either to prevent the need for admission to hospital or to facilitate early supported discharge from hospital [ 16 , 30 32 ]. Some pathways were designed solely for those requiring home oxygen therapy, whereas others offered home oxygen therapy as part of a wider oximetry monitoring programme.…”
Section: Purpose and Scope Of Home Oxygen Monitoring And Therapy Prog...mentioning
confidence: 99%